You never know what you’re recording - Baños, Fernando; Aznar, Yayo (Re-visiones, 2024)
Guidelines for a correct (and reader-friendly) appreciation of the text: this text was not written with consensus of opinion. It is an exchange of ideas through dialogue between an art historian and the creator of a video-essay based on specific images of the war in Bosnia. This ’textual collage’ was presented as a paper during the seminar “Art thinks; thinking with images” in June 2010 and formed part of the R&D project Images of art and the rewriting of narratives in global visual culture. The reader should note that the text in italics identifies comments of the art historian (Yayo Aznar Almazán) whereas normal text is that of the artist (Fernando Baños Fidalgo).